Documentary evidence : issues, conflicts and responses - Ashi, Valentine Bekeh (Abuja, Nigeria : Simitex, 2006)
The book is prepared primarily for the use of students of the Nigerian Law School, who are preparing for the Bar Part II course in evidence law and practice.
Includes footnotes.
oif 11/07/2018, ijb, 28/01/2019
Loans
Keywords: Evidence, Documentary; Civil law; Evidence (Law); Nigeria